CAPITAL INTENSITY DRIVES TAX AGGRESSIVENESS IN INDONESIAN MANUFACTURING - Hindayati , Nurul; Maharani , Rieska; Rusmawati , Zeni (International Journal Multidisciplinary (IJMI), 2024)
General Background: Tax aggressiveness remains a critical concern for policymakers, especially in emerging markets where regulatory frameworks and corporate practices are evolving. Specific Background: Manufacturing companies, particularly in the basic and chemical industries, play a significant role in the economy of Indonesia. Despite their importance, there is limited research on the impact of accounting conservatism, capital intensity, and earnings management on tax aggressiveness within this sector. Knowledge Gap: Previous studies have inconsistently reported the effects of accounting conservatism, capital intensity, and earnings management on tax aggressiveness, with mixed results and limited focus on the Indonesian context. Aims: This study aims to analyze the impact of accounting conservatism, capital intensity, and earnings management on tax aggressiveness among manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Results: Using a sample of 115 observations from 23 companies, the study employed multiple regression analysis with IBM SPSS Statistics Version 25. The findings reveal that accounting conservatism and earnings management do not significantly influence tax aggressiveness, as evidenced by significance values of 0.939 and 0.282, respectively. Conversely, capital intensity is positively associated with tax aggressiveness, with a significance value of 0.018. Novelty: This study contributes to the literature by providing empirical evidence on the specific determinants of tax aggressiveness in the Indonesian manufacturing sector, highlighting the significance of capital intensity while challenging the relevance of accounting conservatism and earnings management in this context. Implications: The results offer valuable insights for stakeholders, including policymakers and regulatory bodies, to refine tax regulations and enforcement strategies, ensuring a more effective approach to managing tax aggressiveness in the manufacturing sector.